(untitled) (Journal of Hama University, 2024)
Introduction: A health indicator is a characteristic of an individual, population or environment that is measured (directly or indirectly) and can be used to describe one or more aspects of the health of the individual or population. Identifying the nutritional and health problems that an autistic child suffers from during his developmental stages is an indicator of his health and nutritional status. The less these problems decrease, the better the child’s nutritional and health condition improves. Many studies confirm the importance of good nutrition and diet in alleviating the symptoms of autism. Objective: The current research aims to evaluate health indicators in children and adolescents with autism spectrum disorder. Research materials and methods: The cross-sectional descriptive quantitative method was used. Data was collected from the Autism Association, Bashaer Al-Nour Association in the city of Latakia, and Al-Majd Association in the city of Tartous/Syria in the period extending from 15/6/2023 to 10/9/2023. A convenience sample was used using a random sample of 55 children and adolescents of both sexes diagnosed with autism spectrum disorder and 55 of their guardians. Results: The results of the current study showed that approximately one-third of autistic children and adolescents suffer from obesity, overweight, and anemia, and more than two-fifths of them suffer from tooth decay, and about one-third of them are at risk of developing cardiovascular disease and type 2 diabetes based on the waist circumference index. To length. Recommendations: The current study recommends the necessity of distributing brochures or booklets on the nutrition of autistic children and adolescents to every family that has an autistic patient and in all autism centers, and conducting comprehensive periodic examinations for autistic patients.